SPIRITUALITAS MANUSIA DALAM GERABAH KOTEMPORER - DWI RAMADONA, Drs. Muzni Ramanto, Dra. Minarsih, M.Sn (Serupa The Journal of Art Education, 2014)
There is erosion of spiritual values among the people of Indonesia and I am interested lifting this phenomenon and visualize it throught the contemporary pottery. The works made of clay as the main medium and added with other materials such as fiber, wood, and iron. The works which I have already made no longer positioned as pottery but more directed at contemporary pottery works or works of contemporary art which is visualized in the form of realism and naturalism style with a certain attitude motion and raised in 7 pieces of work namely 1), (1) Buy 1 Get 3 Free, (2) New Axis Mundi, (3) Nirwana Shortcut, (4) Rest #1, (5) Rest#2, (6) The Die Become Her, (7) The Portal.Kata kunci : spiritualitas, Kotemporer, Gerabah Kotemporer